Spatial trends and sources of PM2.5 organic carbon volatility fractions (OCx) across the Los Angeles Basin. (15th July 2019) - Soleimanian, Ehsan; Mousavi, Amirhosein; Taghvaee, Sina; Sowlat, Mohammad H.; Hasheminassab, Sina; Polidori, Andrea; Sioutas, Constantinos
Abstract: In this study, we used the positive matrix factorization (PMF) model to apportion the sources of organic carbon volatility fractions (OCx ) as well as total OC concentrations in five different locations across the Los Angeles Basin, including West Long Beach, Anaheim, central Los Angeles (CELA), Rubidoux, and Fontana over the period from July 2012 to June 2013. Total OC as well as OC volatility fractions (OC1 -OC4 ), measured with the thermal-optical analysis as part of the fourth Multiple Air Toxics Exposure Study (MATES IV) by the South Coast Air Quality Management District (SCAQMD), in combination with gaseous and particulate source tracers (such as NOx, O3, particulate sulfate, K + /K ratio, and biomass-burning originated black carbon (BCbb )) were used as inputs to the PMF model. A 3-factor solution, including traffic, secondary organic aerosols (SOA), and biomass burning, was found to be the most physically interpretable solution. Average total OC concentrations showed an upward trend from the sites closer to the coast (i.e., 3.7 ± 1.9 μg m −3 at West Long Beach) to inland downwind sites (i.e., 4.8 ± 1.8 μg m −3 at Fontana), especially in the warm season, suggesting the major impact of SOA formation on total OC concentrations. Source apportionment results indicated that traffic is the dominant contributor to OC2 and OC3 fractions, especially at the sites that are near major primary sources such as CELA and West Long Beach, with corresponding contributions of 60 ± 1.0% and 79 ± 1.7% to OC2 and 53 ± 0.9% and 64 ± 1.3% to OC3, respectively. On the other hand, SOA was found to be the dominant contributor to OC4 fraction, especially at the receptor sites located further inland, with corresponding contributions of 66 ± 1.0% in Rubidoux and 56 ± 0.7% in Fontana. Our results also indicated that traffic is the dominant source of total OC concentrations, with an average contribution of 53 ± 2.4% at all the sites, followed by SOA formation and biomass burning, contributing to 40 ± 1.8% and 7 ± 0.8% of total OC concentrations, respectively. The contribution of traffic and biomass burning to total OC concentrations increased during the cold season, while that of SOA became more significant during the warm season when photochemical activities peak. Results from the present study provided important insight on the sources and spatio-temporal variations of OC volatility fractions as well as total OC concentrations in PM2.5 across the Los Angeles Basin. Highlights: Sources of organic carbon (OC) and its fractions (OCx) were identified in LA Basin. Traffic, SOA, and biomass burning were the dominant sources across the LA Basin. Primary emissions were major contributors to OC2 and OC3 at all of the sites. OC4 concentrations were dominated by contributions from SOA formation.